OPTIMALISASI PORTOFOLIO INVESTASI PROGRAM JAMINAN HARI TUA (JHT) PADA PT JAMSOSTEK (PERSERO) - , Benny Setijawan; , Prof. Dr. Abdul Halim, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
PT. Jamsostek (Persero) as organizers of social insurance agency has two main programs, JHT and non JHT. JHT funds of the pension fund program, has the largest share of funds compared to non-JHT. Most of the instruments placed on the JHT fund investments are in the financial sector, especially in the form of deposits, bonds, stocks and mutual funds. Each of these investment instruments has different return and risk. To balance between return and risk faced by the asset allocation strategy is necessary to note, especially to obtain the optimal portfolio. This study examines the preparation of an optimal investment portfolio for JHT program. The data used in this study is secondary data for the measurement of return of each investment instrument, such as: data guaranteeing deposits, yield on government bonds, LQ 45 index and stock mutual funds index to research the period 2005 to 2010. Optimizing the investment portfolio of the four instruments of investment was made by using mean-variance method introduced by Markowitz (1952). The method relies on the parameters of return, variance and covariance of these investment instruments. Through the Markowitz model, the optimization of the portfolio will be obtained through the proportion of funds should be invested in each of these investment instruments. Optimal composition of investment portfolios in order to minimize the risk of the portfolio at JHT program can be achieved by adding the bond portion of the assets. This is due to coefficient of variation of the bond indicates a lower value than other investment instruments, thus providing a lower portfolio risk than the risk of an actual portfolio of PT. Jamsostek (Persero).